Stroke public awareness campaigns have increased ambulance dispatches for stroke in Melbourne, Australia - Bray, Janet; Mosley, I.; Bailey, M.; Barger, B.; Bladin, C. (2011)
Background and Purpose-Launch of the National Stroke Foundation stroke awareness campaigns has occurred annually during Stroke Week (September) since 2004. From 2006, the campaign used FAST (Face, Arm, Speech, Time) with calling an ambulance added in 2007. The aim of this study was to explore the impact of these campaigns on ambulance dispatches for stroke (Medical Priority Dispatch Card 28) in Melbourne, Australia. Methods-A cross-sectional study examining the monthly proportions of ambulance dispatches for stroke between August 1999 and 2010 was conducted. The proportions of dispatches for stroke were used due to increases in the population and in ambulance dispatches over the study period. These proportions were statistically compared for the month before Stroke Week (August) and the month after Stroke Week (October) for each year and seasonal variation was examined. Results-Between 1999 and 2009, the annual proportion of dispatches for stroke increased from 2.1% (n=4327) to 2.95% (n=9918). When stroke dispatches in August were compared with those in October, a significant increase in October was only detected since the call an ambulance message was added to FAST: 2007 (2.62% to 3.00%, P=0.006), 2008 (2.62% to 3.05%, P=0.003), and 2009 (2.70% to 3.09%, P=0.007). From 2005, the peak season for stroke dispatches shifted from winter to spring. Conclusions-Ambulance dispatches for stroke significantly increased after the National Stroke Foundation campaigns began, particularly in years receiving greater funding and featuring the FAST symptoms and the message to call an ambulance. Monitoring ambulance use appears to be an effective measure of campaign penetration. © 2011 American Heart Association, Inc.